Benzyl N-[(Z)-(1-methyl-2-sulfanylpropylidene)amino]carbamodithioate. - Break, Mohammed Khaled; Mehta, Sachin; M. Tahir, M. Ibrahim; Crouse, Karen Anne; Khoo, Teng Jin (International Union of Crystallography, 2013)
The title compound, C12H16N2S3, was obtained by the condensation reaction of S-benzyl dithiocarbazate and 3-mercaptobutan-2-one. The phenyl ring and thiol (SH) group are approximately perpendicular [S—C—C—C and N—C—C—S torsion angles = 67.8 (3) and 116.9 (2)°, respectively] to the rest of the molecule. In the crystal, molecules are linked by weak S—H(...)S and N—H(...)S hydrogen bonds, π–π interactions between the benzene rings [centroid–centroid distance = 3.823 (2) Å] and C—H(...)π interactions.